Community development programme in one Sabah community – An exploratory study / Siti Aishah - Siti Aishah, - (1976)
This study attempts to analysis the impact of the community development programme on the people of Kg. Laba, Kota Klias, Beaufort and to see whether there is any discrepancies between the organiser of the community development programme and the people at the grassroot level in their perception of the programme implemented in the village. Data was collected through structured interviews and informal discussions with the respondents. The study shows that discrepancies to prevail between the organisers and the villagers. Discrepancies are also noted among the different groups of villagers that is the villager-participant (VP) group, the non-villager-participant (VNP) group, the village development committee (VDC) group and the non-VDc group. Views also differ between the older and the younger respondents. The implications of the study are also brought to light and discussed.